ANALISIS FAKTOR-FAKTOR PEMBERDAYAAN PEREMPUAN TERHADAP PENDAPATAN PERKAPITA DI INDONESIA - Meivianti Putri Atinna (2023)
Women's empowerment is a challenge in optimizing human resources, especially women, in productive activities that can increase income and welfare, namely by increasing women's involvement in economic, political and labor life. This is because women's empowerment in Indonesia is still very limited in most provinces in Indonesia. This study aims to determine the effect of women's empowerment factors on per capita income in Indonesia, as a proxy for economic growth. Per capita income is a measure of community welfare that is often used by the government. The research was conducted on 34 provinces in Indonesia in 2017-2021, using the panel data regression analysis method on E-views13 software. The results of the regression analysis in this study indicate that the variables of the Gender Development Index and Women's Wages have a significant positive effect on Per Capita Income, but the variables of the Gender Empowerment Index and the Female Labor Force Participation Rate do not have a significant effect on Per Capita Income. Keywords: Women Empowerment, Per capita income